2012
DOI: 10.1111/j.1365-246x.2012.05583.x
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthal anisotropy beneath southern Africa from very broad-band surface-wave dispersion measurements

Abstract: SUMMARY Seismic anisotropy within the lithosphere of cratons preserves an important record of their ancient assembly. In southern Africa, anisotropy across the Archean Kaapvaal Craton and Limpopo Belt has been detected previously by observations of SKS‐wave splitting. Because SKS‐splitting measurements lack vertical resolution, however, the depth distribution of anisotropy has remained uncertain. End‐member interpretations invoked the dominance of either anisotropy in the lithosphere (due to the fabric formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
66
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 97 publications
14
66
1
Order By: Relevance
“…In an alternative approach, we inverted phase velocities from all single-event measurements within northeastern Tibet for the orientation and amplitude of azimuthal anisotropy within this sub-region, assuming that the structure within it is, approximately, laterally homogeneous (Adam & Lebedev 2012). Regional tomography (e.g., Yang et al 2012;Shen et al 2016, this study) shows a relatively homogeneous region here, supporting this assumption, even though some heterogeneity is certain to be present.…”
Section: Region-average Azimuthal Anisotropymentioning
confidence: 83%
See 1 more Smart Citation
“…In an alternative approach, we inverted phase velocities from all single-event measurements within northeastern Tibet for the orientation and amplitude of azimuthal anisotropy within this sub-region, assuming that the structure within it is, approximately, laterally homogeneous (Adam & Lebedev 2012). Regional tomography (e.g., Yang et al 2012;Shen et al 2016, this study) shows a relatively homogeneous region here, supporting this assumption, even though some heterogeneity is certain to be present.…”
Section: Region-average Azimuthal Anisotropymentioning
confidence: 83%
“…7). The data set, which comprises tens to hundreds of measurements from each station pair, is sorted by azimuth, weighted, and averaged using a 15 • sliding window, in order to remove potential biases due to uneven azimuthal sampling (Adam & Lebedev 2012). At each period, alternative inversions are performed, one for 2ψ anisotropy terms only and another for both 2ψ and 4ψ terms.…”
Section: Region-average Azimuthal Anisotropymentioning
confidence: 99%
“…We measure the shear-wave splitting with the rotation-correlation method in SplitLab (Wuestefeld et al 2010)� The stations at smaller azimuths show a mean fast axis of -46° (defined to be positive away from the T component towards the R component) and a mean splitting time of 1�0 second� Figure 2�8�1: Coverage map of Sdiff phases from a deep Fijian earthquake (Sept� 4th 1997) observed on the Kaapvaal array in southern Africa� Magenta dots mark the entry and exit points to D'' and the green dots bound the diffracted parts of the paths� We interpret the apparent anisotropy to be where the phases turn upwards in the D'' indicated by the striped patch� The background model is SAW24B16 (Megnin and Romanowicz, 2000) at 2800 km depth� Figure 2�8�2: Particle motions for the horizontal velocity components� Waveforms are filtered between 10 and 30 seconds� Time runs from blue to red over 30 seconds� On the right are the observed particle motions at stations of the Kaapvaal array� Most striking are the elliptical particle motions at smaller azimuths� On the left are synthetic particle motions that capture most of the main features of the data (see Results subsection)� The splitting in Sdiff results from the presence of anisotropy in the upward leg of the path after the diffracted part of the path� We separately measure the splitting in the SKS and SKKS phases to exclude an origin of the splitting in the upper mantle� There is little and very scattered splitting in these phases for this event� Other studies of upper mantle anisotropy beneath the Kaapvaal array (e.g., Adam and Lebedev, 2012) show different trends than the shear-diffracted waveforms would suggest here�…”
Section: Methodsmentioning
confidence: 99%
“…Significant variations of SKS delay times were measured near Kimberley, which was interpreted as the boundary between a strongly and a weakly anisotropic domain (Fouch et al, 2004b). More recently, a Rayleigh wave azimuthal anisotropy model (Adam and Lebedev, 2012) proposed that the mantle fabric at lithospheric depths parallels the Archean-Paleoproterozoic crustal structures in the Limpopo belt and in the northern Kaapvaal, but is perpendicular to the crustal structures in the western part of the craton. Vinnik et al (2012), using P receiver functions and SKS waveform inversion, also observed belt-parallel, fast directions in the uppermost mantle near the Limpopo belt.…”
Section: Baptiste and A Tommasi: Seismic Properties Of The Kaapvamentioning
confidence: 99%
“…The deformation of the Kaapvaal craton has also been extensively investigated by seismic anisotropy studies (Silver et al, 2001;Fouch et al, 2004a;Fouch et al, 2004b;Silver et al, 2004;Adam and Lebedev, 2012;Vinnik et al, 1995Vinnik et al, , 2012. Silver et al (2001) measured fast polarization directions that consistently followed the trend of geological structures and small SKS delay times (0.62 s on average), with almost null delays in the central Kaapvaal craton.…”
Section: Baptiste and A Tommasi: Seismic Properties Of The Kaapvamentioning
confidence: 99%